Analysis of Spatial Knowledge Construction Based on Ethnomathematics in Junior High School Student - Rada Irma Mutia; Kamid Kamid; Husni Sabil (MASI Mandiri Edukasi, 2025)
Mathematics is a science that has an important role in dealing with various problems in everyday life. It includes spatial abilities because it involves the ability of students to manipulate objects related to space. However, students' spatial abilities in geometry material are still relatively weak. This study aims to analyze and describe the construction of students' spatial knowledge based on ethnomathematics. This research is qualitative research with a descriptive approach. Data collection techniques in this study include information absorption sheets (reading), tests, and interviews. Data were analyzed using data reduction techniques, presentation, and conclusion drawing. The results showed that S1 could meet the five indicators of spatial ability, where S1 organized his knowledge based on assimilation and accommodation. Furthermore, S2 can meet five indicators of spatial ability and organize his knowledge by assimilation. While S3 only fulfills three indicators of spatial ability, this is due to a lack of accuracy and haste in answering questions. This study's findings show that learning associated with culture can improve students' mathematical abilities in spatial terms.